2021
DOI: 10.1039/d0an02245d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence assay for the determination of glutathione based on a ring-fused 2-pyridone derivative in dietary supplements

Abstract: Herein, a novel fluorescent method for the determination of GSH levels in aqueous solutions involving the utilization of citric acid as a derivatization reagent was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These compounds were successfully studied in several applications. [70][71][72][73][74] In 2018, it was found that upon heating of mixtures of urea and citric or citrazinic acid under anhydrous conditions, a green-emitting fluorophore can be readily obtained, identified as (4-hydroxy-1H-pyrrolo [3,4-c]pyridine-1,3,6(2H,5H)-trione -HPPT). 40 This discovery led to many applications based on green emitting carbon dots containing HPPT on their surface.…”
Section: Cbmfsa Historical Perspectivementioning
confidence: 99%
“…These compounds were successfully studied in several applications. [70][71][72][73][74] In 2018, it was found that upon heating of mixtures of urea and citric or citrazinic acid under anhydrous conditions, a green-emitting fluorophore can be readily obtained, identified as (4-hydroxy-1H-pyrrolo [3,4-c]pyridine-1,3,6(2H,5H)-trione -HPPT). 40 This discovery led to many applications based on green emitting carbon dots containing HPPT on their surface.…”
Section: Cbmfsa Historical Perspectivementioning
confidence: 99%
“…The values of calculated atomic charges and bond lengths are presented in Table 2 , along with the corresponding changes in these values under electronic excitation S 0 → S 1 . From the obtained data, one can see that the total negative charge is distributed dominantly at the oxygen and nitrogen atoms, while the carbon atoms bear the appreciable positive charges because of the polarization of the C-O and C-N bonds [ 35 , 36 , 37 , 38 ]. The electronic excitation S 0 → S 1 of the anionic HPPT molecule causes noticeable redistribution of the electron occupancies at both atoms and bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In the last 20 years, several methods have been proposed for GSH determination, such as methods based on high-performance liquid chromatography (HPLC) (6), UV-Vis spectrophotometry (6), fluorescence spectroscopy (7), and mass spectrometry (8). Despite acceptable sensitivity, some of these methods suffer from practical disadvantages, such as the need for expensive and high-tech instrumentation, time-consuming processes, and complex sample preparation processes.…”
Section: Inroductionmentioning
confidence: 99%